Bullying Survivors: The Dynamic of Frequency, Forms of Bully and The Response of Survivors - Cicilia Tanti Utami; M.G. Adiyanti; Bhina Patria; Wenty Marina Minza (PSIKODIMENSIA, 2020)
This research used a descriptive method to obtain description about the unpleasant experience of students in school. Subjects are 731 students from six high schools in Semarang city. Method of data collection using scale. The results showed that students who admitted to get unpleasant treatment in the frequent category were 21 % and very often 4,2 %. Student who admitted to have physical bullying of 24,9 % (male 65,7%, female 34,3 %), verbal 86,4 % (male 85,7%, female 87%), and social 25,6% (male 21,9 %, female 29,1%). Then the response of students when received unpleasant treatment is silent 56,8 %, trying to prove themselves 55,4% and ignorant 46,7 %. However, most of the survivors admitted quite successfully to overcome the bullying that be received. The descriptive research give further undersanding for researcher about violence in schools, how survivors response and overcome these acts of violence.